A polyurethane structural adhesive
By preparing polyurethane structural adhesives composed of components A and components B, combining the ester exchange reaction and enhancing the optimal filling ratio of thermally conductive fillers, the shortcomings of traditional polyurethane adhesives in terms of hydrolysis, oxidation, weather resistance, temperature resistance, etc. are solved, and the excellent hydrolysis resistance and high-efficiency thermal conductivity of polyurethane structural adhesives are achieved, providing long-term safety guarantees for new energy batteries.
Patent Information
- Application Number
- CN202411668500.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-21
AI Technical Summary
Traditional polyurethane adhesives have shortcomings in their hydrolysis resistance, oxidation resistance, weather resistance, temperature resistance, etc., and it is difficult to meet the stability and safety requirements of new energy batteries in high-frequency vibration, aging, rainwater, ice and snow high-temperature climates.
Polyurethane structural glue consisting of components A and components B are used. Component A includes dimer acid polyester polyol, castor oil polyester polyol, chain extenders, weathering agents and enhanced thermal conductivity fillers. Component B includes trimer isocyanate, tetramethylphenyldimethyldiisocyanate and enhanced thermal conductivity fillers. It is prepared by transesterification reaction, combined with the optimal filling ratio of enhanced thermal conductivity fillers, to improve the hydrolysis, weathering and thermal conductivity of the material.
It realizes the excellent hydrolysis and weather resistance and efficient thermal conductivity of polyurethane structural adhesives, which can provide long-term safety guarantees for new energy batteries and meet the multiple performance requirements of the power battery system for bonding materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of structural adhesive materials, and in particular to a weather-resistant polyurethane structural adhesive for vehicle-mounted power batteries or energy storage batteries and a preparation method thereof. Background Art
[0002] With the rapid development of the new energy lithium battery field, the domestic new energy vehicle and energy storage fields have made great progress, but in the process of development, some engineering problems that need to be solved urgently have also been encountered. For example, the power battery system requires a large amount of materials to solve the stability and safety problems of the vehicle power battery. These materials can basically be divided into structural battery bonding materials, structural thermal conductive materials and insulating materials, which are very critical materials to solve the long-term high-frequency vibration, aging, rain, ice and snow, high temperature climate and other problems encountered by the vehicle power battery during vehicle driving. These difficult problems have posed new challenges to the structural bonding of vehicle power batteries.
[0003] Traditional polyurethane adhesives mainly use polyols derived from petrochemical energy, such as commonly used polyether polyols and polyester polyols, in which polyether polyols are mainly polyether polyols with propylene oxide, ethylene oxide and tetrahydrofuran as the main raw materials; polyester polyols are mainly prepared by dehydration condensation reaction based on small molecule diols and acid anhydrides and long-chain dibasic acids of petrochemical raw materials. In the field of hydrophobic polyols, for example, CN113929888A patent uses linear diols to modify castor oil, CN103113560A uses dibasic acid and linear diols to mix and modify dimer acid, and CN115975148A also uses long-chain diols to prepare the ultra-long carbon chain of dimer acid polyester polyols, and uses the castor oil polyol as a multifunctional crosslinking agent. Therefore, traditional polyether / polyester polyol finished products have many deficiencies in terms of hydrolysis resistance, oxidation resistance, weather resistance, and temperature resistance, and it is difficult to meet the requirements of the rapid development of the automotive industry.
[0004] Many domestic studies have also conducted in-depth research and exploration in the field of vehicle-mounted power batteries and energy storage. For example, CN111303820A uses vegetable oil-based polyols to improve the weather resistance of adhesives, but the thermal conductivity of the thermally conductive filler is low, and the curing agent uses a non-weather-resistant polyisocyanate curing agent, which has low thermal conductivity and poor weather resistance. In CN111995979A, component A includes polyether polyols, chain extenders, and thermally conductive fillers, and component B consists of polyether diols, phenylene polyisocyanates, and thermally conductive fillers. This adhesive material also has the problems of low thermal conductivity and poor adhesion. In addition, component A in CN116239984A includes polyether polyol / polyester polyol and thermal conductive filler, and component B consists of polyether diol, phenylene polyisocyanate and filler; in the polyurethane thermal conductive structural adhesive and its preparation method disclosed in CN116606625A, component A includes polyol, small molecule chain extender, modified thermal conductive filler and catalyst, the polyol is compounded by modified diol and polyether polyol, and component B includes aromatic isocyanate and modified thermal conductive filler.
[0005] The above-mentioned various structural adhesive preparation methods are difficult to meet the increasing requirements of large-scale application of power batteries. This is mainly reflected in the poor weather resistance of chemically synthesized polyether and polyester polyols, the lack of good temperature resistance of aromatic curing agents such as phenylene polyisocyanate, and the difficulty of traditional thermal conductive fillers to meet the increasingly high thermal conductivity requirements, and the dynamic bonding energy is not high. Therefore, simply requiring polyurethane structural adhesives to have good bonding strength and thermal conductivity cannot meet the requirements of their use in new energy batteries. They must also have better resistance to moisture and heat, aging resistance, and meet the lightweight design of automobiles. Summary of the invention
[0006] In order to solve the above technical problems, the solution provided by the present invention can well change the shortcomings of existing products on the market, increase the moisture and heat resistance of the material, and provide excellent protection for the long-term and reliable operation of the battery.
[0007] To achieve the above object, the present invention provides the following specific implementation scheme.
[0008] A polyurethane structural adhesive, consisting of component A and component B;
[0009] The component A comprises the following raw material components by weight:
[0010] 15-25 parts of dimer acid polyester polyol,
[0011] Castor oil polyester polyol 20-35 parts,
[0012] 3-4 parts of chain extender,
[0013] Adhesive catalyst 0.002-0.02 parts,
[0014] 1-2 parts of weathering agent,
[0015] Enhanced thermal conductive filler 40-60 parts,
[0016] Additives 0.3-0.6 parts;
[0017] The B component comprises the following raw material components by weight:
[0018] 30-36 parts of trimer isocyanate,
[0019] Tetramethylxylene diisocyanate (TMXDI) 7-14 parts,
[0020] Isophorone diisocyanate (IPDI) 6-10 parts,
[0021] Enhanced thermal conductive filler 40-60 parts,
[0022] Additives 0.3-0.6 parts;
[0023] The molar ratio of the hydroxyl group in the A component to the isocyanate group in the B component is 1:(1.05-1.25).
[0024] The dimer acid polyester polyol is obtained by mixing dimer acid methyl ester and diol and adding an ester exchange catalyst for reaction.
[0025] Preferably, the dimer acid polyester polyol is prepared from the following raw materials in parts by weight:
[0026] 500-800 parts of methyl dimer,
[0027] 60-100 parts of diol,
[0028] 0.22-0.45 parts of transesterification catalyst.
[0029] In some other embodiments, the raw materials of the dimer acid polyester polyol further include 4-7 parts of an antioxidant.
[0030] The dimer acid methyl ester is refined dimer acid methyl ester with a content of greater than or equal to 99.2%.
[0031] The diol is a cyclic diol, preferably at least one selected from 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, dihydroxyethyl cyclohexyl ether, hydrogenated hydroquinone dihydroxyethyl ether, cyclopentyl dimethanol, octahydro-4,7-methylene-1H-indenedimethanol. More preferably, 18-25 parts of 1,3-cyclohexanedimethanol, 25-45 parts of hydrogenated hydroquinone dihydroxyethyl ether, and 17-30 parts of cyclopentyl dimethanol.
[0032] Specifically, the preparation method of dimer acid polyester polyol comprises the following steps: reflux dimer acid methyl ester, diol, transesterification catalyst and antioxidant under inert gas protection at 67-75°C for 3-6 hours; then control the reaction temperature to 155-165°C, and slowly reflux for 0.5-2 hours; then raise the temperature to 180-200°C and pressure to -0.1 to -0.095Mpa for dealcoholization for 2-4 hours; and cool to obtain dimer acid polyester polyol. The inert gas is nitrogen, helium or argon; preferably nitrogen.
[0033] The castor oil polyester polyol is obtained by mixing methyl ricinoleate and polyol and adding an ester exchange catalyst for reaction.
[0034] Preferably, the castor oil polyester polyol is prepared from the following raw materials in parts by weight:
[0035] 300-500 parts of methyl ricinoleate,
[0036] Polyol 50-100 parts,
[0037] 0.12-0.36 parts of transesterification catalyst.
[0038] The ricinoleic acid methyl ester is refined ricinoleic acid methyl ester with a content of greater than or equal to 97.5%.
[0039] The polyol is a polycyclohexyl diol, preferably at least one selected from hydrogenated bisphenol A, hydrogenated bisphenol F, adamantane diol, 2,7-dihydroxydecahydronaphthalene, and cyclohexanediol, more preferably 20-35 parts of hydrogenated bisphenol A, 10-30 parts of adamantane diol, and 20-35 parts of cyclohexanediol.
[0040] In some other embodiments, the raw material of the castor oil polyester polyol further includes 2-5 parts of an antioxidant.
[0041] Specifically, the method for preparing castor oil polyester polyol comprises the following steps: methyl ricinoleate, polyol, transesterification catalyst and antioxidant are refluxed at 67-75°C for 3-6 hours under the protection of inert gas; then the reaction temperature is controlled at 165-175°C, and the reaction is slowly refluxed for 0.5-2 hours; then the temperature is raised to 190-220°C and the pressure is -0.1 to -0.095Mpa for dealcoholization for 2-3 hours; and castor oil polyester polyol is obtained after cooling. The inert gas is nitrogen, helium or argon; preferably nitrogen.
[0042] The above-mentioned transesterification catalyst is selected from at least one of lithium hexafluorophosphate, tetraethylammonium hydroxide, tetramethylammonium hydroxide, pyridine butane sulfonic acid hydrogen sulfate ionic liquid, imidazole propane sulfonic acid hydrogen sulfate ionic liquid, and acidic ZSM molecular sieve catalyst; preferably lithium hexafluorophosphate, tetraethylammonium hydroxide, and tetramethylammonium hydroxide; more preferably lithium hexafluorophosphate or tetramethylammonium hydroxide.
[0043] The above antioxidant is preferably a bisphosphite.
[0044] The hydroxyl values of the dimer acid polyester polyol and castor oil polyester polyol are both 46-210 mgKOH / g, and the acid values are both 0.2-0.5 mgKOH / g.
[0045] The specific advantage of the above two polyester polyols is that after the ester exchange is completed, the ester exchange catalyst can be heated to a high temperature to decompose, and there will be no residual catalytic effect to cause adverse effects on the subsequent adhesive configuration caused by excessive reaction speed.
[0046] Preferably, the chain extender is a diol with less than 10 carbon atoms and a methyl or polymethylene steric hindrance near the hydroxyl group to improve the anti-hydrolysis stability. In some specific embodiments, the chain extender is selected from at least one of 2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 2-butyl-1,3-propanediol, 2,3-dimethyl-1,4-butanediol, and 2-methyl-1,4-butanediol. The chain extender is more preferably a mixture of 2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, and 2,3-dimethyl-1,4-butanediol in a mass ratio of 1: (1-2): (1-3).
[0047] Preferably, the adhesive catalyst is selected from at least one of an organic silver catalyst (ESCAT#100Ag-1822), a BCAT series organic bismuth, a ZCAT series organic zinc, and a BX series bismuth-zinc composite catalyst. Organic silver catalysts and BX series bismuth-zinc composite catalysts are preferred.
[0048] Preferably, the weathering agent is selected from at least one of carbodiimide and 8-hydroxyquinolinone. More preferably, the weathering agent is a composite weathering agent composed of carbodiimide and 8-hydroxyquinolinone in a mass ratio of (2-1):1.
[0049] Preferably, the enhanced thermal conductive filler is selected from at least one of activated alumina-coated silver nanowires, boron nitride, high α-phase micron alumina balls (>99.8%), high α-phase nano alumina balls (>99.8%), aluminum hydroxide, and activated aluminum hydroxide. Among them, the activated alumina-coated silver nanowires have an aspect ratio of 115, the high α-phase micron alumina balls have a D50 of 12um, and the high α-phase nano alumina balls have a D50 of 170nm.
[0050] The auxiliary agent is selected from one or more of a defoamer, a leveling agent, and a wetting and dispersing agent. Specifically, such as defoamer BYK-A530, leveling agent BYK-310, and wetting and dispersing agent BYK-9076. More preferably, the auxiliary agent is composed of defoamer BYK-A530, leveling agent BYK-310 and wetting and dispersing agent BYK-9076, and the weight ratio is 1:1:2.
[0051] Preferably, the trimer isocyanate is selected from at least one of pentamethylene diisocyanate trimer (PDI trimer) and hexamethylene diisocyanate isocyanurate trimer (HDI trimer). In some specific embodiments, the NCO content of the PDI trimer is 21.7%, the NCO content of the HDI trimer is 21.8%, the NCO content of tetramethylxylylene diisocyanate is 33.8%, and the NCO content of isophorone diisocyanate is 37.6%.
[0052] The present invention also provides a method for preparing the polyurethane structural adhesive, comprising the following steps:
[0053] (1) After uniformly mixing dimer acid polyester polyol, castor oil polyester polyol, chain extender, weathering agent, enhanced thermal conductive filler and auxiliary agent according to parts by weight, the adhesive catalyst is added and mixed uniformly, and the material is discharged to obtain component A;
[0054] (2) According to parts by weight, trimer isocyanate, tetramethylxylene diisocyanate (TMXDI), isophorone diisocyanate (IPDI), enhanced thermal conductive filler and additives are uniformly mixed to obtain component B.
[0055] The component A and the component B are packaged separately, and when used, are mixed in a molar ratio of hydroxyl groups in the component A to isocyanate groups in the component B of 1:(1.05-1.25), and then cured at room temperature.
[0056] Compared with existing product technologies, the polyurethane structural adhesive of the present invention starts with the selection of raw materials and designs a hydrophobic molecular structure, which has excellent interfacial wetting and bonding effects on low surface energy materials, especially on PP / PE and aluminum substrates; the design concept of hydrolysis resistance and high bonding is still continued in the formulation design process; during the implementation process, the enhanced thermal conductive filler is further used through particle size calculation to achieve the best filling ratio, improve the phonon transmission and vibration energy transfer of the XYZ axis plane, and thus realize heat conduction. Therefore, the polyurethane structural adhesive of the present invention has excellent hydrolysis resistance and weather resistance as well as excellent thermal conductivity, which can provide safety protection for the long-term use of new energy batteries. DETAILED DESCRIPTION
[0057] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0059] 1) Preparation of dimer acid polyester polyol (A1)
[0060] Preparation of Dimer Acid Polyester Polyol A1-1
[0061] 700g of dimer acid methyl ester and 95.0g of diol (including 25g of 1,3-cyclohexanedimethanol, 40g of hydrogenated hydroquinone dihydroxyethyl ether, and 30g of cyclopentyl dimethanol) were added to a reactor equipped with a stirring device, a methanol separation cooler, an inert nitrogen protection device, a high-temperature thermometer and a precise electric heating jacket, and 0.36g of a catalyst lithium hexafluorophosphate and 5g of an antioxidant diphosphite were added at the same time. The temperature was gradually raised to 70°C and refluxed for 3 hours, and stirring was continued during the process to obtain a light yellow transparent solution; then the reaction temperature was controlled to 160°C, and the reaction was slowly refluxed for 1 hour; heating was continued, and when the temperature of the reactor reached 180°C, the pressure was adjusted to -0.095Mpa to start dealcoholization, the temperature was raised to 200°C and kept at this temperature for 2 hours until the excess diol was basically evaporated, and the heating was stopped; when the temperature was reduced to 80°C, the reaction product was poured out to obtain a light brown transparent dimer acid polyester polyol A1-1.
[0062] It was determined that the acid value of product A1-1 was 0.39 mgKOH / g and the hydroxyl value was 112 mgKOH / g.
[0063] Preparation of Dimer Acid Polyester Polyol A1-2
[0064] 500g of dimer acid methyl ester and 60.0g of diol (including 18g of 1,3-cyclohexanedimethanol, 25g of hydrogenated hydroquinone dihydroxyethyl ether, and 17g of cyclopentyl dimethanol) were added to a reactor equipped with a stirring device, a methanol separation cooler, an inert nitrogen protection device, a high-temperature thermometer and a precise electric heating jacket, and 0.22g of a catalyst tetramethylammonium hydroxide and 4g of an antioxidant diphosphite were added at the same time. The temperature was gradually raised to 67°C and refluxed for 6 hours, and stirring was continued during the process to obtain a light yellow transparent solution; then the reaction temperature was controlled to 155°C, and the reaction was slowly refluxed for 2 hours; heating was continued, and when the temperature of the reactor reached 180°C, the pressure was adjusted to -0.095Mpa to start dealcoholization, the temperature was raised to 200°C and kept at this temperature for 4 hours until the excess diol was basically evaporated, and the heating was stopped; when the temperature was reduced to 80°C, the reaction product was poured out to obtain a light brown transparent dimer acid polyester polyol A1-2.
[0065] It was determined that the acid value of product A1-2 was 0.56 mgKOH / g and the hydroxyl value was 54 mgKOH / g.
[0066] Preparation of Dimer Acid Polyester Polyol A1-3
[0067] 500g of dimer acid methyl ester and 95.0g of diol (including 25g of 1,3-cyclohexanedimethanol, 40g of hydrogenated hydroquinone dihydroxyethyl ether, and 30g of cyclopentyl dimethanol) were added to a reactor equipped with a stirring device, a methanol separation cooler, an inert nitrogen protection device, a high-temperature thermometer and a precise electric heating jacket, and 0.25g of a catalyst tetraethylammonium hydroxide and 5g of an antioxidant diphosphite were added at the same time. The temperature was gradually raised to 75°C and refluxed for 4 hours, and stirring was continued during the process to obtain a light yellow transparent solution; then the reaction temperature was controlled to 165°C, and the reaction was slowly refluxed for 0.5 hours; heating was continued, and when the temperature of the reactor reached 180°C, the pressure was adjusted to -0.1Mpa to start dealcoholization, the temperature was raised to 200°C and kept at this temperature for 2 hours until the excess diol was basically evaporated, and the heating was stopped; when the temperature was reduced to 80°C, the reaction product was poured out to obtain a light brown transparent dimer acid polyester polyol A1-3.
[0068] It was determined that the acid value of product A1-3 was 0.5 mgKOH / g and the hydroxyl value was 163 mgKOH / g.
[0069] Preparation A1-4
[0070] The difference between the preparation methods A1-4 and A1-1 is that lithium hexafluorophosphate is replaced by dibutyltin dilaurate, and the other steps are the same as the preparation method A1-1.
[0071] Preparation A1-5
[0072] The difference between the preparation methods A1-5 and A1-1 is that the amount of lithium hexafluorophosphate used is 1.0 g, and the other steps are the same as the preparation method A1-1.
[0073] It was determined that the acid value of the A1-4 product was 1.35 mgKOH / g and the hydroxyl value was 112 mgKOH / g.
[0074] It was determined that the acid value of the A1-5 product was 1.05 mgKOH / g and the hydroxyl value was 92 mgKOH / g.
[0075] 2) Preparation of castor oil polyester polyol (A2)
[0076] Preparation of Dimer Acid Polyester Polyol A2-1
[0077] 468g of methyl ricinoleate and 67.5g of polyol (20g of hydrogenated bisphenol A, 27.5g of adamantanediol, and 20g of cyclohexanediol) were added to a reactor equipped with a stirring device, a methanol separation cooler, an inert nitrogen protection device, a high-temperature thermometer, and a precise electric heating jacket. At the same time, 0.23g of catalyst lithium hexafluorophosphate and 4g of antioxidant diphosphite were added. The temperature was gradually raised to 70°C and refluxed for 3 hours with continuous stirring during the process to obtain a light yellow transparent solution. The reaction temperature was then controlled to 170°C and the reflux reaction time was slowly 1 hour. The heating was continued. When the temperature of the reactor reached 190°C, the pressure was adjusted to -0.095Mpa to start dealcoholization, the temperature was raised to 210°C, and the reaction was kept at this temperature for 2 hours until the excess polyol was basically evaporated, and the heating was stopped. When the temperature dropped to 80°C, the reaction product was poured out to obtain a golden transparent polyester polyol A2-1.
[0078] It was determined that the acid value of the product was 0.28 mgKOH / g and the hydroxyl value was 110 mgKOH / g.
[0079] Preparation of Dimer Acid Polyester Polyol A2-2
[0080] 300g of methyl ricinoleate and 65g of polyol (25g of hydrogenated bisphenol A, 20g of adamantanediol, and 20g of cyclohexanediol) were added to a reactor equipped with a stirring device, a methanol separation cooler, an inert nitrogen protection device, a high-temperature thermometer, and a precise electric heating jacket. At the same time, 0.12g of catalyst tetramethylammonium hydroxide and 2g of antioxidant diphosphite were added. The temperature was gradually raised to 67°C and refluxed for 6 hours with continuous stirring during the process to obtain a light yellow transparent solution. The reaction temperature was then controlled to 165°C and the reflux reaction time was slowly 2 hours. The heating was continued. When the temperature of the reactor reached 190°C, the pressure was adjusted to -0.1Mpa to start dealcoholization, the temperature was raised to 210°C, and the reaction was kept warm at this temperature for 3 hours until the excess polyol was basically evaporated, and the heating was stopped. When the temperature dropped to 80°C, the reaction product was poured out to obtain a golden transparent polyester polyol A2-1.
[0081] It was determined that the acid value of the product was 0.6 mgKOH / g and the hydroxyl value was 170 mgKOH / g.
[0082] Preparation of Dimer Acid Polyester Polyol A2-3
[0083] 446g of methyl ricinoleate and 38g of polyol (15g of hydrogenated bisphenol A, 10g of adamantanediol, 13g of cyclohexanediol) were added to a reactor equipped with a stirring device, a methanol separation cooler, an inert nitrogen protection device, a high-temperature thermometer and a precise electric heating jacket, and 0.36g of catalyst tetraethylammonium hydroxide and 5g of antioxidant diphosphite were added at the same time. The temperature was gradually raised to 75°C and refluxed for 4 hours with continuous stirring during the process to obtain a light yellow transparent solution; then the reaction temperature was controlled to 175°C and the reaction time was slowly refluxed for 0.5 hour; heating was continued, and when the temperature of the reactor reached 190°C, the pressure was adjusted to -0.1Mpa to start dealcoholization, the temperature was raised to 220°C, and the reaction was kept at this temperature for 2 hours until the excess polyol was basically evaporated, and the heating was stopped; when the temperature was reduced to 80°C, the reaction product was poured out to obtain a golden transparent polyester polyol A2-1.
[0084] It was determined that the acid value of the product was 0.35 mgKOH / g and the hydroxyl value was 56 mgKOH / g.
[0085] Preparation A2-4
[0086] The difference between the preparation methods A2-4 and A2-1 is that lithium hexafluorophosphate is replaced by isopropyl titanate, and the other steps are the same as the preparation method A2-1.
[0087] Preparation A2-5
[0088] The difference between the preparation methods A2-5 and A2-1 is that the amount of lithium hexafluorophosphate used is 1.0 g, and the other steps are the same as the preparation method A2-1.
[0089] It was determined that the acid value of A2-4 product was 1.18 mgKOH / g and the hydroxyl value was 121 mgKOH / g.
[0090] It was determined that the acid value of the A2-5 product was 1.09 mgKOH / g and the hydroxyl value was 100 mgKOH / g.
[0091] 3) Preparation of structural adhesive
[0092] Preparation of component A: according to the formula, put A1, A2, enhanced thermal conductive filler, chain extender, weathering agent and additives into a 2L planetary power mixer, heat to 40°C within 30 minutes, evacuate and stir for 2 hours (speed 100 rpm, dispersion speed 800 rpm), add adhesive catalyst after cooling to room temperature, continue stirring for 5 minutes under vacuum, discharge and seal to obtain component A.
[0093] The above-mentioned preparation method of component A was used to prepare the components A of Examples 1A to 6A shown in Table 1.
[0094] Table 1 Composition of Component A of Examples 1A to 6A
[0095]
[0096] Comparative Example 1A
[0097] The difference between Comparative Example 1A and Example 1A is that A1-1 is replaced by A1-4, and the other steps are the same as the preparation method of component A in Example 1A.
[0098] Comparative Example 2A
[0099] The difference between Comparative Example 2A and Example 1A is that A1-1 is replaced by A1-5, and the other steps are the same as the preparation method of component A in Example 1A.
[0100] Comparative Example 3A
[0101] The difference between Comparative Example 3A and Example 1A is that A2-1 is replaced by A2-4, and the other steps are the same as the preparation method of component A in Example 1A.
[0102] Comparative Example 4A
[0103] The difference between Comparative Example 4A and Example 1A is that A2-1 is replaced by A2-5, and the other steps are the same as the preparation method of component A in Example 1A.
[0104] Comparative Example 5A
[0105] The difference between Comparative Example 5A and Example 1A is that A1-1 is replaced with Asahi Kasei T5651 polycarbonate polyol, and the other steps are the same as the preparation method of component A in Example 1A.
[0106] Comparative Example 6A
[0107] The difference between Comparative Example 6A and Example 1A is that A2-1 is replaced by PO3G H1000, and the other steps are the same as the preparation method of component A in Example 1A.
[0108] Comparative Example 7A
[0109] The difference between Comparative Example 7A and Example 1A is that the thermally conductive reinforcing filler is replaced with an equal amount of spherical silicon powder, and the other steps are the same as the preparation method of component A in Example 1A.
[0110] Preparation of component B: Add trimer isocyanate, TMXDI, IPDI, enhanced thermal conductive filler and additives into a 2L planetary power mixer according to the formula, stir for 60 minutes under vacuum (rotation speed 100 rpm, dispersion speed 600 rpm), and seal and package to obtain component B.
[0111] The above-mentioned preparation method of component B was used to prepare the components B of Examples 1B to 8B shown in Table 2.
[0112] Table 2 Composition of component B of Example 1B to Example 6B
[0113]
[0114] Comparative Example 1B
[0115] The difference between Comparative Example 1B and Example 1B is that the PDI trimer and the HDI trimer are replaced by an equal amount of TMXDI, and the other steps are the same as the preparation method of component B in Example 1B.
[0116] Comparative Example 2B
[0117] The difference between Comparative Example 2B and Example 1B is that TMXDI is replaced by an equal amount of IPDI, and the other steps are the same as the preparation method of component B in Example 1B.
[0118] Comparative Example 3B
[0119] The difference between Comparative Example 3B and Example 1B is that IPDI is replaced by an equal amount of TMXDI, and the other steps are the same as the preparation method of component B in Example 1B.
[0120] Comparative Example 4B
[0121] The difference between Comparative Example 4B and Example 1B is that the thermally conductive reinforcing filler is replaced with an equal amount of spherical silicon powder, and the other steps are the same as the preparation method of component B in Example 1B.
[0122] The A components of the above-mentioned Examples 1A to 6A and the B components of Examples 1B to 6B as shown in Table 3 were packaged separately to prepare the polyurethane structural adhesives of Examples 1-7.
[0123] Table 3 Composition of polyurethane structural adhesive of Examples 1-7
[0124] composition Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Component A Example 1A Example 2A Example 3A Example 4A Example 5A Example 6A Example 4A Component B Example 1B Example 2B Example 3B Example 4B Example 5B Example 6B Example 2B
[0125] The A component and the B component shown in Table 4 were packaged separately to prepare the structural adhesives of Comparative Examples 1-7.
[0126] Table 4 Composition of structural adhesives of Comparative Examples 1-7
[0127]
[0128] When in use, the hydroxyl group in component A and the isocyanate group in component B are mixed in a molar ratio of 1:1.15, and then cured at room temperature.
[0129] The following performance tests were performed on the polyurethane structural adhesives of Examples 1-7, the structural adhesives of Comparative Examples 1-7, commercially available 1 (Jitai-polyurethane thermal conductive adhesive structural adhesive S5391 series), and commercially available 2 (Huitian polyurethane thermal conductive adhesive structural adhesive 8659 series).
[0130] Tensile strength and elongation at break: Tested according to GB / T1040.1-2006 method and the average value of 3 times is taken.
[0131] Shear strength: Tested according to GB / T 7124-2008 method and the average value of 3 times is taken.
[0132] Thermal conductivity: Refer to ASTM D5470 method to test thermal conductivity.
[0133] Resistance to moisture and heat aging: Refer to GB / T 3512-2019 to test the retention rate of moisture and heat aging resistance for 3000 hours.
[0134] Vibration fatigue test: By simulating the vibration of the vehicle under different road conditions, the durability and fatigue life of the automotive materials are tested. The load is 200kg, the frequency is 10KHZ, and it is 10 million times. If the colloid does not break, it passes the test.
[0135] Electrolyte resistance: Soak in electrolyte (cyclic carbonate) at 85°C for 72 hours; if the edge does not turn white, swell, or warp, the test is passed (pass).
[0136] The performance test results of Examples 1-7, Comparative Examples 1-7, Commercially Available 1, and Commercially Available 2 are shown in Table 5.
[0137] Table 5 Performance test results
[0138]
[0139] It can be seen from the test results in Table 5 that the polyurethane structural adhesive of the present invention in Examples 1-7 has better vibration fatigue resistance and / or electrolyte resistance and / or aging retention rate than the structural adhesive of the comparative example. Compared with commercially available products, it has better vibration fatigue resistance in fatigue tests, is more suitable for vehicle-mounted anti-vibration structural bonding, and has a lower density than commercially available products, which is more conducive to vehicle-mounted lightweight design; in addition, the polyurethane structural adhesive of Examples 1-7 of the present invention has good comprehensive mechanical properties in terms of tensile strength and bonding shear strength of the cured product after 24 hours of room temperature curing, which are better than commercially available products. It can be seen that the polyurethane structural adhesive of the present invention has excellent mechanical properties while achieving good lightweight and thermal conductivity, and can meet the long-term use and weather resistance requirements of the thermal conductive structural adhesive of new energy battery packs.
[0140] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A polyurethane structural adhesive, characterized in that: It is composed of component A and component B; The component A comprises the following raw material components by weight: 15-25 parts of dimer acid polyester polyol, Castor oil polyester polyol 20-35 parts, 3-4 parts of chain extender, Adhesive catalyst 0.002-0.02 parts, 1-2 parts of weathering agent, Enhanced thermal conductive filler 40-60 parts, Additives 0.3-0.6 parts; The dimer acid polyester polyol is prepared from the following raw materials in parts by weight: 500-800 parts of methyl dimer, 60-100 parts of diol, 0.22-0.45 parts of transesterification catalyst; The castor oil polyester polyol is prepared from the following raw materials in parts by weight: 300-500 parts of methyl ricinoleate, Polyol 50-100 parts, 0.12-0.36 parts of transesterification catalyst; The transesterification catalyst is selected from at least one of lithium hexafluorophosphate, tetraethylammonium hydroxide and tetramethylammonium hydroxide; The B component comprises the following raw material components by weight: 30-36 parts of trimer isocyanate, 7-14 parts of tetramethylxylylene diisocyanate, 6-10 parts of isophorone diisocyanate, Enhanced thermal conductive filler 40-60 parts, Additives 0.3-0.6 parts; The trimer isocyanate is selected from at least one of pentamethylene diisocyanate trimer and hexamethylene diisocyanate isocyanurate trimer; The enhanced thermal conductive filler is selected from at least one of activated alumina-coated silver nanowires, high α-phase micron alumina balls, and high α-phase nano alumina balls; The molar ratio of the hydroxyl group in the A component to the isocyanate group in the B component is 1:(1.05-1.25).
2. The polyurethane structural adhesive according to claim 1, characterized in that: The dimer acid polyester polyol is obtained by mixing dimer acid methyl ester and diol and adding an ester exchange catalyst to react; the castor oil polyester polyol is obtained by mixing ricinoleic acid methyl ester and polyol and adding an ester exchange catalyst to react.
3. The polyurethane structural adhesive according to claim 1, characterized in that: The diol is selected from at least one of 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, dihydroxyethyl cyclohexyl ether, hydrogenated hydroquinone dihydroxyethyl ether, cyclopentyl dimethanol, and octahydro-4,7-methylene-1H-indenedimethanol; the polyol is selected from at least one of hydrogenated bisphenol A, hydrogenated bisphenol F, adamantane diol, 2,7-dihydroxydecahydronaphthalene, and cyclohexanediol.
4. The polyurethane structural adhesive according to claim 3, characterized in that: The raw materials of the dimer acid polyester polyol also include 4-7 parts of antioxidants; the raw materials of the castor oil polyester polyol also include 2-5 parts of antioxidants.
5. The polyurethane structural adhesive according to any one of claims 1 to 4, characterized in that: The chain extender is selected from at least one of 2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 2-butyl-1,3-propanediol, 2,3-dimethyl-1,4-butanediol and 2-methyl-1,4-butanediol.
6. The polyurethane structural adhesive according to claim 5, characterized in that: The adhesive catalyst is selected from at least one of an organic silver catalyst, a BCAT series organic bismuth catalyst, a ZCAT series organic zinc catalyst, and a BX series bismuth-zinc composite catalyst.
7. The polyurethane structural adhesive according to claim 5, characterized in that: The weathering agent is selected from at least one of carbodiimide and 8-hydroxyquinolinone.
8. The polyurethane structural adhesive according to claim 5, characterized in that: The auxiliary agent is selected from one or more of a defoamer, a leveling agent, and a wetting and dispersing agent.
Citation Information
Patent Citations
Preparation method of dimer acid type polyester polyol
CN103113560A
Bi-component polyurethane structural adhesive for bonding power batteries and preparation method thereof
CN111303820A
Polyurethane heat-conducting structural adhesive capable of being quickly cured at room temperature
CN111995979A
Dimer acid polyester polyol as well as preparation method and application thereof
CN113929888A
Two-component polyurethane heat-conducting structural adhesive for bonding battery module structure and preparation method of two-component polyurethane heat-conducting structural adhesive
CN116239984A